FORECASTING UZBEKISTAN’S GDP BY AUTOREGRESSIVE INTEGRATED MOVING AVERAGE (ARIMA) MODEL - Azibaev , Akhmadkhon (Techscience uz - Topical Issues of Technical Sciences, 2025)
This paper is about the ARIMA (Auto-Regressive Integrated Moving Average) model to forecast Uzbekistan’s GDP for the period 2025–2030, with country’s economic trajectory . GDP is a critical measure of economic activity, reflecting the monetary value of all goods and services produced within a nation. The analysis emphasizes the importance of forecasting GDP for effective policymaking, resource allocation, and investment planning. Results indicate a general upward trend in Uzbekistan’s GDP, with occasional fluctuations. The ARIMA model demonstrates robust predictive capabilities, aligning with historical patterns and current economic reforms. Despite its reliability, the study highlights potential improvements through hybrid approaches incorporating external factors